2016
DOI: 10.1044/2016_jslhr-l-15-0242
|View full text |Cite
|
Sign up to set email alerts
|

Orthography and Modality Influence Speech Production in Adults and Children

Abstract: Purpose: The acquisition of literacy skills influences the perception and production of spoken language. We examined if orthography influences implicit processing in speech production in child readers and in adult readers with low and high reading proficiency. Method: Children (n = 17), adults with typical reading skills (n = 17), and adults demonstrating low reading proficiency (n = 18) repeated or read aloud nonwords varying in orthographic transparency. Analyses of implicit linguistic processing (segmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 54 publications
1
22
1
Order By: Relevance
“…Lower STI values are indicative of a smaller deviation from the underlying pattern (i.e., greater stability; Smith, Goffman, Zelaznik, Ying, & McGillem, 1995). Previous studies have demonstrated that both PCC and STI can quantify the progression of motor speech development and directly index the influences of syntactic, lexical, phonological, and orthographic characteristics on implicit processing (e.g., Goffman, Gerken, & Lucchesi, 2007;Heisler et al, 2010;McMillan et al, 2009;Saletta et al, 2015Saletta et al, , 2016Smith & Goffman, 1998).…”
Section: Speech Production Indexes Implicit Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…Lower STI values are indicative of a smaller deviation from the underlying pattern (i.e., greater stability; Smith, Goffman, Zelaznik, Ying, & McGillem, 1995). Previous studies have demonstrated that both PCC and STI can quantify the progression of motor speech development and directly index the influences of syntactic, lexical, phonological, and orthographic characteristics on implicit processing (e.g., Goffman, Gerken, & Lucchesi, 2007;Heisler et al, 2010;McMillan et al, 2009;Saletta et al, 2015Saletta et al, , 2016Smith & Goffman, 1998).…”
Section: Speech Production Indexes Implicit Learningmentioning
confidence: 99%
“…Traditionally, increased articulatory stability is considered to be indicative of more skillful and efficient processing within the individual, of defining healthy speakers versus clinical populations, and of responding to lower task demands (e.g., Brumbach & Goffman, 2014;Goffman & Smith, 1999;Green, Moore, Higashikawa, & Steeve, 2000;Kleinow & Smith, 2000;Nip & Green, 2013;Walsh & Smith, 2011). Our previous works indicated that adults, both typical and low-proficiency readers, demonstrated increased phonetic accuracy when enabled to read, rather than just hear, nonword stimuli (Saletta et al, 2015(Saletta et al, , 2016. Adults with low reading proficiency also demonstrated increased speech movement stability when enabled to read the nonword stimuli in an orthographically transparent spelling, rather than in an orthographically opaque spelling.…”
Section: Speech Production Indexes Implicit Learningmentioning
confidence: 99%
See 3 more Smart Citations